Sintesa Precipitated Calcium Carbonate (PCC) Dari Cangkang Kerang Darah (Anadara Granosa) Dengan Variasi Ukuran Partikel Dan Waktu Karbonasi - Lucy Rahmawati; Amun Amri; Zultiniar Zultiniar; Yelmida Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Precipitated Calcium Carbonate (PCC) is a product of the processing of natural materials containing calcium carbonate resulting from the precipitation process with high purity. Bloodcockle shell can be used as a source of calcium for precipitated Calcium Carbonate. The purpose of this study to produce PCC of waste shells blood with carbonation method and determine the particle size of the PCC and the best carbonation time. Synthesis performed using carbonation method by adding nitric acid to the slaking process. Blood cockle shell samples prior shells calcined at a temperature of 900°C for 3 hours to form calcium oxide and then dissolved with nitric acid (slaking process) with a particle size variation CaO (+ 20-60; + 60- 100; +100-120) mesh forming CaNO3, then added ammonia to pH 12, the next process of Ca (OH)2 CO2 gas flowing until the time was varied (0.5, 1, 1.5) hours to form a white precipitate which is precipitated Calcium Carbonate. The use of inorganic acids in this study aims to improve the solubility of CaO in the slaking process so that a high yield of the products obtained.The highest yield of PCC obtained at treatment +100-120 mesh particle size and carbonation time of 1.5 hours, with the percentage yield of 88.58%. Results of analysis Atomic Absorption Spectrophotometry (AAS) obtained CaCO3 content of 76.6%. From the pattern of X-ray diffraction (XRD) and Scanning Electron Microscopy (SEM) can be seen form the resulting crystal is a mixture vaterit and calcite.Keywords : Blood cockle shell, Method of Carbonation , PCC , Particle Size , ,Time Carbonation